Simulation of Fidelity in Entanglement-Based Networks with Repeater Chains - David Pérez Castro; Ana Fernández Vilas; Manuel Fernández Veiga; Mateo Blanco Rodríguez; Rebeca P. Díaz Redondo (Applied Sciences)
We implement a set of simulation experiments in NetSquid specifically designed to estimate the end-to-end fidelity across a path of quantum repeaters or quantum switches. The switch model includes several generalizations that are not currently available in other tools and are useful for gaining insight into practical and realistic quantum network engineering problems: an arbitrary number of memory registers at the switches, simplicity in including entanglement distillation mechanisms, arbitrary switching topologies, and routing protocols. An illustrative case study is presented, namely a comparison in terms of performance between a repeater chain where repeaters can only swap sequentially and a single switch equipped with multiple memory registers that is able to handle multiple swapping requests.